2020
DOI: 10.5937/straman2001029d
|View full text |Cite
|
Sign up to set email alerts
|

Regression analysis of the impact of internal factors on return on assets: A case of meat processing enterprises in Serbia

Abstract: The aim of this paper is to identify and measure the impact of internal factors on the business success of meat processing enterprises expressed through profitability. Panel analysis was constructed for the sample which includes 24 enterprises in Serbia at the period from 2007 to 2016. The accounting rate of Return on assets (ROA), as a measure of productivity, was in function of the dependent variable, while the size of the enterprise, age, debt ratio, quick ratio, inventory, sale growth and capital turnover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
3
13
0
Order By: Relevance
“…Theorists agree with the statement that a good level of profitability is present when the ROA indicator is higher than 10% (Dakić & Mijić, 2020). Having in mind the above, the condition that theory finds as a reference value of profitability was not met.…”
Section: Resultsmentioning
confidence: 78%
“…Theorists agree with the statement that a good level of profitability is present when the ROA indicator is higher than 10% (Dakić & Mijić, 2020). Having in mind the above, the condition that theory finds as a reference value of profitability was not met.…”
Section: Resultsmentioning
confidence: 78%
“…Although long-term sources of financing are particularly important because they reflect the capital structure and affect the long-term financing stability, due to the willingness of companies to use short-term financing to finance long-term projects, the use of indicators that include only long-term debt could provide a misleading picture of a firm's risk in relation to financial debt (Damodaran, 2007). Therefore, in a large number of empirical studies, measures involving total debts are used to express capital structure (Abor, 2007;Dakić & Mijić, 2020;Khan, 2012;Salim & Yadav, 2012;San & Heng, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…In most of the company's performance measures (return on assets, return on equity and earnings per share), a negative relationship was found with all analysed indicators of capital structure, while in the case of Tobin's Q, a significantly positive relationship was identified between this indicator and short term debt as well as long term debt. A significant study on a sample of companies from the Republic of Serbia was conducted by Dakić & Mijić (2020). The authors found, among other things, that debt ratio, as a measure of the extent of a company's leverage, has a significant negative impact on return on assets.…”
Section: Theoretical Background and Review Of Previous Empirical Researchmentioning
confidence: 99%
“…Manufacturing sector is one of the largest waste generators. In addition to environmental issues, such as waste, economic issues must be taken into account in this sector, such as quick ratio and sales growth which have significant positive impact on profitability of manufacturing companies (Dakić & Mijić, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%